Kazakhstan's energy cooperation with Russia - Cohen, Ariel (Global market briefings., 2006)
This important study explains how Russia, with its private sector and policy makers working in tandem, has exerted a significant amount of control over Kazakhstan's vast natural resources and its economic freedom. It looks at the way Russia and Kazakhstan agreed to divide the Caspian Sea shelf and how Kazakhstan has managed to maintain good relations with Moscow overall, despite its insistence on exporting energy resources to China and Europe directly and its hopes to export through Iran.